Peran Layanan Bimbingan Konseling dalam Mendukung Perkembangan Siswa di SMAN 1 Lemahabang Karawang - Tia Amelda Febriani; Vini Emilia Putri; Zahra Nuriyah; Nur Aini Farida; Vina Naura Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe the role of guidance and counseling (BK) services in supporting the development of students at SMAN 1 Lemahabang Karawang. The focus of the study includes four main areas: academic development, personal development, social development, and the development of students' potential. This study employs a qualitative descriptive approach with data collection techniques through observation and semi-structured interviews involving BK teachers and two twelfth-grade students. The results of the study show that BK services provide an important contribution to increasing learning motivation, discipline, and students' career planning. In addition, BK services also play a role in shaping character and social skills through an empathetic approach and collaboration with Islamic Religious Education teachers in the implementation of religious activities and moral guidance. Although there are still some students who have a less positive view of the guidance and counseling services, in general, they assess that the implementation of guidance and counseling services at SMAN 1 Lemahabang has been effective and has a positive impact on students' personal development.